2014
DOI: 10.1111/aor.12255
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurements of Energy Augmentation for Mechanical Circulatory Assistance in a Patient-Specific Fontan Model

Abstract: A mechanical blood pump specifically designed to increase pressure in the great veins would improve hemodynamic stability in adolescent and adult Fontan patients having dysfunctional cavopulmonary circulation. This study investigates the impact of axial-flow blood pumps on pressure, flow rate, and energy augmentation in the total cavopulmonary circulation (TCPC) using a patient-specific Fontan model. The experiments were conducted for three mechanical support configurations, which included an axial-flow impell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…No retrograde velocities in the SVC were observed in this study, even at the highest rotational speed. This finding correlates previous results with regard to hydraulic testing of the same TCPC vessel configuration . Increasing the mixing that naturally occurs in the TCPC junction while removing the venous congestion, not activating or causing blood trauma, and not overloading a failing single ventricle are important steps toward restoring hemodynamic stability in these patients.…”
Section: Discussionsupporting
confidence: 88%
“…No retrograde velocities in the SVC were observed in this study, even at the highest rotational speed. This finding correlates previous results with regard to hydraulic testing of the same TCPC vessel configuration . Increasing the mixing that naturally occurs in the TCPC junction while removing the venous congestion, not activating or causing blood trauma, and not overloading a failing single ventricle are important steps toward restoring hemodynamic stability in these patients.…”
Section: Discussionsupporting
confidence: 88%
“…Hydraulic testing of these configurations was accomplished in Chopski et al. and found that the addition of the stents significantly affected the pressure generation of the pump. The a gainst‐with stent demonstrated a higher pressure generation and increase in flow over the selected range of rotational speeds, than either the super‐diffuser stent or the impeller alone.…”
Section: Discussionmentioning
confidence: 99%
“…A hydraulic flow loop (Fig. ) was used to circulate the experimental fluid through the anatomic Fontan model at the predetermined cardiac output level . To match the refractive index of clear urethane resin, a mixture of diethyl phthalate and ethanol (Sigma‐Aldrich Co., LLC, St. Louis, MO, USA, CAS: 84‐66‐2 and CAS: 64‐17‐5) was determined to match the material refractive index of 1.49 of the TCPC model.…”
Section: Methodsmentioning
confidence: 99%
“…The device is intended for short‐term MCS of up to 4 weeks with percutaneous pump replacement. The development of this device has been successful with computational analyses, PIV studies, and hemolysis testing leading to advanced designs .…”
Section: New Mcs Devices Under Developmentmentioning
confidence: 99%